JENIS IKAN LAUT DALAM DI PERAIRAN TELUK MANADO SULAWESI UTARA - Erly Kaligis (JURNAL PESISIR DAN LAUT TROPIS, 2020)
The aims of this study was to determine the types of fish in the deep sea ecosystem in the Manado Bay area, and to measure the water quality (temperature and salinity) at the study site. The study began with exploration of deep sea locations in Manado Bay, then determined the location of the station consisting of 3 fishing points determined randomly. Determination of depth using the Fish Finder. The method used in obtaining deep sea fish species is the Jigging technique. This technique uses artificial bait with a base of tin, stainless steel wire and a hologram. Some of the data measured from the research are fish species, morphometrics, and water quality. Based on water quality data (temperature and salinity), the waters of Manado Bay have sea surface temperatures ranging from 28.00C and 29.70C and surface salinity in the waters ranges from 33.19 ppt and 34.67 ppt. The types of deep sea fish obtained were 7 species spread out at station 1 there were 4 species consisting of Brama australis, Thysites atun, Lepidocybium flavobrunneum, Sphyraena barracuda, Gymnosarda unicolor, Carcharodon carcharias, Gempylus serpens. The number of fish recorded from the research is 41 individuals. The most common type found was Thyrsites atun, which consisted of 25 individuals spread out at stations 2 and 3.Keywords: fish in the deep sea, Jigging technique, temperature, salinityÂ